LEAD PROFILE OF MONETARY INDICATORS FOR INDIAN GROWTH CYCLES - Dr. Sumanpreet Kaur (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The present paper is an attempt towards recognizing the leading indicators from monetary sector for Indian economy. The growth cycles have been observed by Bry-Boschan (BB) Procedure, utilizing information on Index of Industrial Production (IIP). The respective Composite Leading Index (CLI) has been constructed using Narrow Money (M1) and Time Deposits- Scheduled Commercial Deposits (TDSCB). For the construction of CLI, Auto Regressive Distributed Lag Model (ARDL) is applied. It was found that India has experienced four growth cycles for the time span from June, 1997 to December, 2016. CLI recorded lead with average duration of 2.5 months for IIP peak and 3 months for IIP trough.